Hands-on Workshop on Cryobiology and Assisted Reproductive Technologies (ARTs) in the Laboratory Mouse (Journal of Laboratory Animal Science, 2024)
Animal models are important in biomedical research for validation of in vitro results, conducting proof of concept studies,  and investigating the variety of disease processes and therapeutic targets that help in narrowing the gap between bench  and bedside. The advent of precise genome engineering technologies has allowed the generation of an increasing number  of novel and complex genetically engineered mouse models that can be made available to the scientific and research  community. It is important to also provide access to efficient technologies to safely archive, protect, manage, and maintain  these precious mouse models. Assisted Reproductive Technologies (ARTs) are emerging as an important tool in the  strategic management of vivariums, which involves animal welfare, disaster preparedness, cost minimization, and most  importantly, reproducible research.
Keywords: 3Rs; Cryopreservation; Cryorepository; ARTs; Sperm and Embryo cryopreservation; Hands-on workshop; skill India